Island of the mad eaudiobook - King, Laurie R. (Mary Russell and Sherlock Holmes, 2018)
Mary Russell and Sherlock Holmes untangle the slippery threads of insanity and deadly secrets as they investigate a disappearance in the New York Times bestselling series that Lee Child called "the most sustained feat of imagination in mystery fiction today." A June summer's evening, on the Sussex Downs, in 1925. Mary Russell and Sherlock Holmes are strolling across their orchard when the telephone rings: an old friend's beloved aunt has failed to return following a supervised outing from Bedlam. After the previous few weeks-with a bloody murder, a terrible loss, and startling revelations about Holmes,Russell is feeling a bit unbalanced herself. The last thing she wants is to deal with the mad, and yet, she can't say no. The Lady Vivian Beaconsfield has spent most of her adult life in one asylum after another, yet she seemed to be improving-or at least, finding a point of balance in her madness. So why did she disappear? Did she take the family's jewels with her, or did someone else? The Bedlam nurse, perhaps? The trail leads Russell and Holmes through a lunatic asylum's stony halls to the warm Venice lagoon, where ethereal beauty is jarred by Mussolini's Blackshirts, where the gilded Lido set may be tempting a madwoman, and where Cole Porter sits at a piano, playing with ideas.